Measurement of the tt̄ production cross section in pp collisions at 7 TeV in lepton+jets events using b-quark jet identification - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2011)
A new measurement of the inclusive production cross section for pp→tt̄ is performed at a center-of-mass energy of 7 TeV using data collected by the CMS experiment at the LHC. The analysis uses a data sample corresponding to an integrated luminosity of 36pb-1, and is based on the final state with one isolated, high transverse momentum muon or electron, missing transverse energy, and hadronic jets. The tt̄ content of the selected events is enhanced by requiring the presence of at least one jet consistent with b-quark hadronization. The measured cross section is 150±9(stat)±17(syst)±6(lumi)pb and is in agreement with higher-order QCD calculations. The combination of this measurement with a previous CMS result based on dileptons gives 154±17(stat+syst) ±6(lumi)pb. © 2011 CERN.